Gid man kunne have bragt en tegning! Om definitioner og illustrationer i ensproglige ordbøger - Hovmark, Henrik (Nordiske Studier i Leksikografi, 2010)
This article discusses the actual and possible use of illustrations in monolingual dictionaries. The lexicographic description of concrete objects is taken as the point of departure. The typical elements in definitions of concrete objects are defined, and it is shown that illustrations are especially well-suited for passing on information about the object’s form, construction, components and functioning. In this respect illustrations can be of great help not only for dictionary users but also for the editors in the editing process. Furthermore, the use of illustrations in a wider perspective is touched upon: illustrations can also be used to describe processes and states (verbs), semantic fields, typical situations of use, and experiences associated with the specific lexical item in question. It is argued that a notion of relative distance, i.e. the relative knowledge of the described object, is important in the analysis of and practical work with illustrations in dictionaries.